MARS/NDRI/KSU Communications Workshop: Part 7E. Strategic Crisis Communications-Managing Mycotoxin Risk - Morris, Jeffery B. (My University, 2022)
Communicating about the mycotoxin threat to Nepal’s food supply, requires the science community, public authorities and professional communicators.
Keywords: Aflatoxin; Food Safety; Mycotoxins; Nepal; Public Health; Risk Communication